Synthesis and characterisation of metallopolyamide complexes - Taleb, Robin (2012)
Platinum(II) and ruthenium(II)-based complexes that contain imidazole, pyrrole and β-alanine subunits, capable of recognising specific DNA base-pair sequences, have been synthesised. These polyamides, two platinum(II), [Cl(NH3)2Pt-L6-β-Ala-Py-L4-Im]+ (HSP-2), and [Cl(NH3)2Pt-L6-β-Ala-PyPyPy-L4-ImImIm]+ (HSP-6) and two ruthenium, Δ and Λ-[β-Ala-Py-L4-Im-β-dpq-Ru(phen)2]2+ (Δ and Λ-RUP1), were designed to recognise DNA sequences up to seven base-pairs in length. They were obtained in good yield by a combination of solid and solution phase chemistries. The chirality of the ruthenium precursors Δ- and Λ-[Ru(phen)2(phendo)]2+ was conserved throughout the synthesis. Characterisation was achieved using NMR, UV–Vis and ESI-MS and CD for Δ- and Λ-RUP1. Cytotoxicity was not determined for HSP-2 or HSP-6, due to insolubility, however the IC50 values of Δ and Λ-RUP1 were confirmed to be greater than 40 μM (at an incubation time of 48 h). LD studies indicated that the ruthenium complexes interact with ct-DNA through a mixed binding mode, which is influenced by complex concentration and chirality.